(untitled) (Slavic Studies, 2025)
The text deals with the contemporary state of the Proto-Slavic pronoun *vьsь in the Macedonian language. This pronoun is analyzed in terms of form, as well as in terms of usage. In terms of form, it belongs to the development path followed by South Slavic languages, but it has developed its own specific feature - it is always used with an article. As for usage, plural forms function as indicators of collective reference, while singular forms act as adjectives with the meaning ‘whole’.